Literatur Riview Tentang Faktor Penyebab Klaim Tidak Layak Bayar BPJS Kesehatan Di Rumah Sakit Tahun 2020 - Oktamianiza; Rahmadhani; Yulfa Yulia; Helmi Mazra Putri (Akademi Perekam dan Informasi Kesehatan Imelda, 2021)
The amount of payment made by BPJS Kesehatan to health facilities is determined based on an agreement between BPJS Kesehatan and the relationship of health facilities in the area where the health facilities are located and refers to the INA-CBG's tariff standard. During the leveraging process by the BPJS verifier, several claims were found, one of which was an unfeasible claim. Therefore, the researchers are interested in further examining the factors that cause the BPJS health unfit claims at the hospital. The purpose of this review literature is to describe the factors that cause claims for not worth paying BPJS health at the hospital in 2020. The literature review research uses descriptive analysis which is carried out by describing the facts. The library sources used are 4 libraries from journals. Analyze the data by looking for several groups (comparing), inequality (contrasting), views (criticizing), comparing (synthesizing) and summarizing (summarizing) the research. Based on a review of 4 journals on the appropriateness of the Participation Administration an average of 66%, the suitability of service administration as much as 25%, the accuracy of disease diagnosis as much as 75%, the accuracy of the main diagnosis and the accuracy of the secondary diagnosis as much as 88%, the accuracy of the diagnosis code was 55% correct and the effect of the administrative completeness of the claim requirements on average is still <75%, which means that the administrative completeness of the BPJS Health requirements is still incomplete because it does not meet the BPJS Health standards and regulations in the submitted requirements file. Based on the results of the study, it can be ignored that the administrative completeness of the BPJS Health claim requirements in the hospital is still incomplete, due to the perception of perceptions between internal verifiers and external verifiers, the knowledge and responsibilities of health service workers on the importance of filling in complete, accurate and trustworthy medical record files. . So the researchers suggest that there is periodic socialization to equalize perceptions about policies and standards in the process of submitting BPJS Health claims between internal verifiers and external verifiers and health service workers who participate in filling out medical record files so that problems related to claims not worth paying can be minimized so that services health can run well and smoothly.